Rail Transportation 2003
DOI: 10.1115/imece2003-55122
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Collision Safety Associated With Conventional and Crash Energy Management Cars Mixed Within a Consist

Abstract: A collision dynamics model of a passenger train-to-passenger train collision has been developed to simulate the potential safety hazards and benefits associated with mixing conventional and crash energy management (CEM) cars within a consist. This paper presents a comparison of estimated injuries and fatalities for seven collision scenarios based upon the variable mix of conventional and CEM cars. Based on the analysis results, recommended car placement when mixing cars within a consist is identified. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…The study results presented in this paper, in combination with the study results presented in [2,3], show that CEM cars can be introduced into service with minimum risks and with great potential benefit. Previous studies have shown that the crashworthiness performance of a consist which is a mix of conventional and CEM equipment is never worse than the performance of an all conventional equipment consist in a trainto-train collision, and is always better when a CEM car is the impacting cab car.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The study results presented in this paper, in combination with the study results presented in [2,3], show that CEM cars can be introduced into service with minimum risks and with great potential benefit. Previous studies have shown that the crashworthiness performance of a consist which is a mix of conventional and CEM equipment is never worse than the performance of an all conventional equipment consist in a trainto-train collision, and is always better when a CEM car is the impacting cab car.…”
Section: Discussionmentioning
confidence: 71%
“…The CEM force crush concept can be viewed as a series of steps, as shown in Figure 3. The CEM curve used for this study is a specific design suggested in [3]. There are other design possibilities that would have the necessary force/crush behavior.…”
Section: Structural Design Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the rail passenger equipment crashworthiness research, studies have been conducted to evaluate the influence of operational factors in train-to-train collisions [19,20,21]. These studies show that CEM cars can be introduced into service with minimum risks and with great potential benefit.…”
Section: Discussionmentioning
confidence: 99%
“…FRA may then propose alternative design strategies to better protect the occupied space of passengers and crewmembers and limit the forces that they are subjected to as they ride out a collision or derailment. In addition to developing alternative design strategies, effectiveness studies were also conducted to demonstrate the potential safety benefits for incremental inclusion of structural and/or interior crashworthiness features [1,2].…”
Section: Introductionmentioning
confidence: 99%